Soft hands: An analysis of some gripping mechanisms in soft robot design. (July 2015) - Zhou, Xuance; Majidi, Carmel; O'Reilly, Oliver M.
Abstract: In contrast to their more rigid counterparts, soft robots have the ability to gently grip and maneuver objects with open-loop kinematic control. Guided by several recent designs and implementations of soft robot hands, the present paper analyzes a rod-based model for the fingers in the hand of a soft robot. We show precisely how gripping is achieved and how the performance can be affected by varying the system's parameters. The designs we are interested in feature pneumatic control of the soft robot and we model this actuation as a varying intrinsic curvature profile of the rod. Our work provides a framework for the theoretical analysis of the soft robot and the resulting analysis can also be used to develop some design guidelines.